Spawning-related movements in a salmonid appear timed to reduce exposure to visually oriented predators. (December 2020) - Finlay, Ross W.; Poole, Russell; French, Andrew S.; Phillips, Karl P.; Kaufmann, Joshka; Doogan, Aisling; Cotter, Deirdre; McGinnity, Philip; Reed, Thomas E.
Abstract : Animals often exhibit extensive flexibility in movement behaviours on a range of temporal and spatial scales in response to cues that reliably predict fitness outcomes. The annual timing of movements between distinct habitats can be crucial, particularly in seasonal environments with narrow ecological windows of opportunity. In polygamous species, sexual selection may further shape sex-specific phenology and movement behaviours. Here, we characterized seasonal, daily and diel movement patterns in adult brown trout, Salmo trutta, between a lake feeding habitat and two spawning streams in northwestern Ireland, using passive integrated transponder (PIT) telemetry. Antennae positioned at the inflow and outflow of the lake were used to monitor movements of 197 lake-tagged adults between lake and stream habitats. Across 2 years in both streams, movements were overwhelmingly nocturnal and exhibited distinct seasonality, with a peak in daily detections close to the winter solstice. In both streams, seasonal movement activity of males began and peaked before that of females (protandry). Daily detection probabilities for both sexes increased as the moon waned (decreasing lunar illumination) and as river depth increased, the latter being associated with reduced water clarity. These findings are consistent with fish favouring movement between fluvial and lacustrine habitats when light (both solar and lunar) or hydrological conditions decrease their exposure to visually oriented predators. The observed protandry also suggests a role for intrasexual male competition, whereby earlier male arrival could increase mating opportunities. Highlights: Brown trout males move from feeding lakes to spawning streams before females. While length of activity period is similar, males conduct more frequent movements. Transitional movements of both sexes are primarily nocturnal. Movement probability increases as river height increases and the moon wanes.